Performance analysis of the pending interest table in the cellular network with reservation and retrials. Issue 4 (1st July 2020) - Chung, Shun‐Ping; Pai, Hui‐Yu; Lin, Chia‐Hsin; Lin, Guan‐Ting
Abstract : To solve the inefficient use of internet protocol (IP) addresses in the current host‐centric internet, the content‐centric networking (CCN) replaces the IP address with the content name and the cache memory is used to store data temporarily on each router. One of the key components in CCN is the pending interest table (PIT). When an interest arrives at a CCN node, the node searches the PIT entries for the same request. If no, the node searches the PIT for an idle entry and a request is sent. If there is no idle entry, the request is blocked. If yes, the aggregation mechanism is performed. To prevent the request from becoming out‐of‐date, the timeout mechanism is adopted. In this work, the authors focus on the performance analysis of PIT in the cellular network with two classes of interests, new and handoff interests. To provide service differentiation, a reservation mechanism is adopted. Furthermore, interests may enter the retrial queue and wait to retry later. First, the authors derived the analytical model for the system considered. Second, the impact of various system parameters on the performance measures is studied. Last but not least, computer simulation is written to verify the accuracy of the analytical results.